A fluorinated compound used as migrated photoinitiator in the presence of air. (5th August 2015) - Zhang, Yuxuan; He, Yong; Yang, Jinliang; Zhang, Xueqin; Bongiovanni, Roberta; Nie, Jun
Abstract: A fluorinated photoinitiator, namely perfluorooctanoyl acid 2- [4-(2-hydroxy-2-methyl-propionyl)-phenoxy]-ethyl ester (F-2959) was synthesized and characterized. To increase the polymerization rate, fluorine groups were connected to the benzene ring rather than the hydroxyalkyl. Real time FTIR analysis was taken to study the ability of F-2959 to overcome oxygen inhibition. UV–vis absorption spectroscopy, XPS, SEM, and multi-channel thermo detector were used to prove the migration of F-2959 in the formulations. During photopolymerization, the oxygen inhibition could be obviously decreased as the large amount of photoinitiator at the surface could consume oxygen in the air atmosphere. The fluorine compounds gathering on the surface also reduced the surface energy. By using this strategy, the film surface develops a wrinkled pattern with a low surface energy. And the wrinkled pattern may prove very useful in photopolymerization. Graphical abstract: Highlights: A migratory fluorinated photoinitiator has been used to overcome oxygen inhibition. This initiator had a gradient distribution in the formula. This initiator could lead to better photopolymerization on surface in air. Compared to 1173F, F-2959 had a higher polymerization rate. F-2959 could lead to folds and change the wettability of the polymer surface.